Ponarodela pesem - Golež Kaučič, Marjetka (Traditiones (Ljubljana), 1999)
Based on an analysis of several typical examples of literary poems the articledeals with the transformation of literary poems into folk poetry since the 18th century. The author tries to discover the characteristics of such poems, their authors, or why they became so popular among the people. She concludes that a number of aspects (the poem's contents, manner of expression,melody, variants) are needed in order to transform a poem into a popular song sung by many.
Keywords: Ethnopoetics; ljudske pesmi; slovstvena folklora; Slovene literature; slovenska književnost